Analysis of Figurative Language and Educational Values in Queen Band Songs - Ishaq, Ahmad Yugita; Syarifudin, Syarifudin; Rahmat, Hery (Edulitics (Education, Literature, and Linguistics) Journal, 2023)
This study describes the figurative language and educational values in the Queen band song. The aims of this research were divided into two parts, firstly, to know the figurative language that is used in Queen band songs. secondly, to know what educational values are found in the songs. In this research, the researcher applied a qualitative approach with a descriptive qualitative method. The data for this research was taken from the lyrics video official Queen band on the YouTube channel. The data were collected through an enumeration system based on Bugin’s theory which covers some steps namely simple binary coding. The researcher used the triangulation method which consists whit decontextualization, recontextualization, categorization, and compilation. The data analysis covers five steps: classifying and coding sentences, analyzing the types of figurative language and educational values, drawing the table, verifying, and concluding. The result of this research The researcher found out there are 59 figurative languages from six selected songs by the Queen band, which included: 3 similes, 13 metaphors, 3 synecdoche, 3 metonymies, 10 symbols, 10 allegories, 3 paradoxes, 4 hyperboles, and 10 ironies. the researcher found 19 values of being such as 2 honesties, 10 braveries, 3 confident and potential, and 4 purities. Also, the researcher found there is one value of giving which is loyalty.